Optimization of synthesis constituents of slow-release zinc fertilizers using response surface methodology - Ava Mohrazi; Reza Ghasemi-Fasaei (PLoS ONE, 2026)
Zinc (Zn) deficiency in calcareous soils is a global issue that affects agricultural yields and threatens nutrient availability worldwide. The present study examined optimization of elements influencing synthesis of a slow-release fertilizer (SRF) of Zn and compared it with commercial ZnSO 4 fertilizer. In this study, response surface methodology (RSM) optimization technique was used to reduce costs and time. Organic (pectin, biochar), inorganic (layer double hydroxide (LDH), layer double hydroxide (LDO)), and microbial (bacterial inoculation) treatments were utilized, leading to production of 12 slow-release fertilizers. Ultimately, optimization and modeling were carried out. Based on RSM findings, three fertilizers exhibiting highest Zn levels and greatest desirability (SRF-LDH, SRF-LDO-bacterial, SRF-biochar-LDO-bacterial) were recognized as most efficient fertilizers. LDH increased Zn concentration by 75% and 50% compared to LDO and biochar, respectively. Based on the results, biochar increased Zn concentration by 40% compared to pectin. Additionally, combining biochar with LDH increased Zn concentration by 60% compared to biochar alone. The highest Zn concentration of SRFs (93.48 mg g −1 ) was related to run 3 (organic material: 0, inorganic material: LDH, inoculation bacteria with fertilizer: 1 W/V), which is 3.9-fold higher than the lowest run (24.54 mg g −1 ) (run 9: organic material: pectin, inorganic material: 0, inoculation bacteria with fertilizer: 0). In comparing all runs, where biochar is used instead of pectin in SRFs, the Zn concentration increased. The highest swelling ratio was related to SRF1 (4.4 g g -¹). The swelling ratio of SRF3 (LDO-biochar-bacterial) was 3.81 g g -¹, which was higher than that of ZnSO 4 (2.41 g g -¹). The slow-release behavior of Zn from SRFs demonstrated three phases, comprising an initial phase of steady Zn release and a concluding phase of diminishing Zn release rates. First-order and Higuchi models were appropriate for characterizing slow-release nutrient processes of SRFs, suggesting external environment can affect gradual release of Zn from SRFs. Based on the RSM optimization results, three formulations—SRF-LDH, SRF-LDO-bacterial, and SRF-biochar-LDO-bacterial—were identified as the most efficient among the twelve synthesized SRFs, exhibiting the highest Zn loading and desirability values.